Kritik Ibn Jawzi terhadap Ulama dalam Kitab Talbis Iblis - Rafid Abbas (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2009)
In this paper we are concerned with elaborating the critiques of Ibn Jawzi against the ulama of his time in his Talbis Iblis. By the ulama Ibn Jawzi means the learned in any field of knowledge such as Qur??nic reading (qira?ah), prophetic tradition (hadith), jurisprudence (fiqh), language, letter, and the art of speech (khitabah). We will analyze the motif behind Ibn Jawzi?s warning to the ulama that they can ?by virtue of their knowledge- be manipulated by the Satan. Not all knowledge is therefore good. Hence, we are interested in exposing the nature of knowledge in Ibn Jawzi?s concept and what are the kinds of knowledge that may lead to Satanic manipulation. The paper will also discuss Ibn Jawzi?s advice to the ulama so that they may not fall victim in the trap of the Satan.